Performance of concrete reinforced with jute fibers (natural fibers): A review - Ahmad, Jawad; Arbili, Mohamed Moafak; Majdi, Ali; Althoey, Fadi; Farouk Deifalla, Ahmed; Rahmawati, Cut (Journal of engineered fibers and fabrics, 2022)
Natural fibers are an excellent alternative since they are inexpensive and easily accessible in fibrous form. Several researchers claim that jute fiber (JTF) can be used in concrete to improve its strength and durability performance. This review describes the characteristics and potential uses of some jute fibers in concrete. The main theme of this review is to summarize the effect of JTF on fresh properties of concrete, strength parameters, and durability characteristics. It can be concluded that jute fibers improved strength and durability aspect but decreased the fluidity of concrete in a similar way to synthetic fibers. However, there is little research available on the durability of concrete reinforced with JTF. Furthermore, the optimum percentage of JTF in concrete is critical as the higher dose adversely affects strength and durability characteristics due to lack fluidity. The typical range of optimum dose of JTF varies from 1% to 2% depending on the length and diameter of jute fibers. The review also identifies the key for future researchers to further, enhance the properties of concrete reinforced with JTF.